2022
DOI: 10.3390/jpm12020189
|View full text |Cite
|
Sign up to set email alerts
|

Does 3D Printing-Assisted Acetabular or Pelvic Fracture Surgery Shorten Hospitalization Durations among Older Adults?

Abstract: Acetabular or anterior pelvic ring fractures are rare but extremely complicated and challenging injuries for orthopedic trauma surgeons. Three-dimensional (3D) printing technology is widely used in the management of these two fracture types for surgical benefits. Our study aimed to explore whether 3D printing-assisted acetabular or pelvic surgery is beneficial in terms of shortening the length of hospital stay (LHS) and intensive care unit (ICU) stay (ICU LS) for older patients. This retrospective study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In our study, it was found that the LHS could not be shortened with 3D assistance in pelvic or acetabulum fracture patients. Our past research found that in the elderly population, the presence or absence of 3D usage did not shorten the LHS [22]. This study discovered that, in the group with 3D assistance, LHS was significantly associated with the duration from admission to pelvic or acetabular surgery.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In our study, it was found that the LHS could not be shortened with 3D assistance in pelvic or acetabulum fracture patients. Our past research found that in the elderly population, the presence or absence of 3D usage did not shorten the LHS [22]. This study discovered that, in the group with 3D assistance, LHS was significantly associated with the duration from admission to pelvic or acetabular surgery.…”
Section: Discussionmentioning
confidence: 51%
“…We found that age had no effect on the LHS. Our previous study also found no significant relationship between LHS and age in the elderly population with or without 3D printing assistance [22]. In younger men, the average bone mineral density was within normal range, giving their bones better strength and impact resistance.…”
Section: Discussionmentioning
confidence: 70%